The politics of constructionism - Velody, Irving; Williams, Robin, 1946- (Social Theory Series., 1998)
"The Politics of Constructionism" presents a broadranging and critical overview of the many themes of social constructionism and its relevance to contemporary social and political issues. Clearly structured and bringing together leading international contributors from across the social sciences, it offers an invaluable may through this rich body of literature. Major questions and topics explored in its critique and application of constructionist ideas include the theory and practice of scientific method, the development of social and political policy, the use of social science statistical methods, self-identity and the politics of collective identities, and technological advances in reproductive medicine. Drawing on insights from psychology, sociology, politics, philosophy, cultural, gender, and social studies, "The Politics of Constructionism" links the discourse of constructionism to the wider social and political world and offers much to suggest that, contrary to the final impoverishment claimed by some of postmodernism, social science is witnessing the beginning of a new enrichment. It will be essential reading for all students and academics interested in social constructionism and contemporary issues and debates across the social sciences.